Desain pembelajaran RME untuk menstimulasi kemampuan berpikir kritis dan literasi numerasi siswa MTs - Nur Rosaini, Della; Handayani, Ratih (International Journal of Progressive Mathematics Education, 2025)
This study aims to test the effectiveness of a Realistic Mathematics Education (RME)-based learning design in stimulating critical thinking and numeracy literacy in Islamic Junior High School (Islamic Junior High School) students. This study used a quantitative method with a quasi-experimental Non-Equivalent Control Group design. The subjects consisted of seventh-grade students divided into an experimental class and a control class. The experimental class implemented the RME learning design, assisted by worksheets (LKPD), which emphasized progressive mathematization processes through the stages of model-of, model-for, and formal representation, while the control class used conventional learning. The research instrument was a descriptive test of numeracy literacy and critical thinking, which had been tested for validity and reliability. The results of the N-Gain analysis showed an increase in student abilities in the moderate category, with the experimental class achieving higher achievement than the control class, although the difference was not statistically significant. These findings indicate that the RME learning design has the potential to improve students' activeness, critical reasoning, and contextual numeracy understanding, but requires a longer implementation period to have a significant impact.   Penelitian ini bertujuan dan menguji efektivitas desain pembelajaran berbasis Realistic Mthematics Education (RME) dalam menstimulasi kemampuan berpikir kritis dan literasi numerasi siswa Madrasah Tsanawiyah. Penelitian ini menggunakan metode kuantitatif dengan desain quasi eksperimen tipe Non-Equivalent Control Group. subjek penelitian terdiri atas siswa kelas VII yang dibagi ke dalam kelas eksperimen dan kelas kontrol. Kelas eksperimen menerapkan desain pembelajaran RME berbantuan LKPD yang tekanan proses matematisasi progresif melalui tahapan model-of, model-for, dan representasi formal, sedangkan kelas kontrol menggunakan pembelajaran konvensional. Instrumen penelitian berupa tes uraian literasi numerasi dan berpikir kritis yang telah diuji validitas dan reliabilitasnya. Hasil analisis N-Gain menunjukkan peningkatan kemampuan siswa pada kategori sedang, dengan pencapaian kelas eksperimen lebih tinggi di bandingkan kelas kontrol, meskipun perbedaannya belum signifikan secara statistik. Temuan ini menunjukkan bahwa desain pembelajaran RME berpotensi meningkatkan keaktifan, penalaran kritis, dan pemahaman numerasi kontekstual siswa, namun memerlukan durasi implementasi yang lebih panjang agar berdampak signifikan